2021
DOI: 10.1002/csc2.20351
|View full text |Cite
|
Sign up to set email alerts
|

Seedbank seeds for the study of environmentally induced transgenerational epigenetic variability: A case study of barley

Abstract: Transgenerational epigenetics inheritance refers to the possibility to inherit epigenetic-based information acquired from previous generations. The design of experiments that can measure this phenomenon presents complexities. These are related mainly to difficulties in the identification of epigenetic variation components that are independent from genetic variation, and to difficulties related to the time needed to expose genetically stable plants to different environments for several generations. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
1
0
0
Order By: Relevance
“…While a large fraction of epigenetic variation, at least in plants, appears to be dependent on the genome, a smaller yet significant fraction is often found to be better explained by the environment than the underlying genetic structure. This result has been observed for DNA methylation across taxonomically diverse natural populations of plants (De Kort et al, 2020;Jueterbock et al, 2020;Martinelli et al, 2021) and animals (Aagaard et al, 2022;Chapelle & Silvestre, 2022;Johnson & Kelly, 2020). In two of the most recent comprehensive population epigenetic studies of plants, most epigenetic variation was found to be genetic in origin (~90%-95% in CG, ~70%-90% in CHG and 55%-65% in CHH), but the environment still explained a significant fraction of the observed variation (~5%-10% in CG, 10%-30% in CHG and 15%-25% in CHH; Figure 2) (Galanti et al, 2022;Sammarco et al, 2024).…”
Section: The Genetic and Environmental Determinants Of Natural Epigen...supporting
confidence: 62%
“…While a large fraction of epigenetic variation, at least in plants, appears to be dependent on the genome, a smaller yet significant fraction is often found to be better explained by the environment than the underlying genetic structure. This result has been observed for DNA methylation across taxonomically diverse natural populations of plants (De Kort et al, 2020;Jueterbock et al, 2020;Martinelli et al, 2021) and animals (Aagaard et al, 2022;Chapelle & Silvestre, 2022;Johnson & Kelly, 2020). In two of the most recent comprehensive population epigenetic studies of plants, most epigenetic variation was found to be genetic in origin (~90%-95% in CG, ~70%-90% in CHG and 55%-65% in CHH), but the environment still explained a significant fraction of the observed variation (~5%-10% in CG, 10%-30% in CHG and 15%-25% in CHH; Figure 2) (Galanti et al, 2022;Sammarco et al, 2024).…”
Section: The Genetic and Environmental Determinants Of Natural Epigen...supporting
confidence: 62%